2013
DOI: 10.7243/2052-4358-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients in dental settings at risk of cardiovascular disease and diabetes

Abstract: Background: The purpose of our study was to identify patients in a dental setting at risk of already having or developing high blood pressure or high plasma glucose, investigate possible associations between these conditions and periodontal status and explore the correlation between screening results and follow-up assessments concerning the need for medical treatment and/or lifestyle changes performed by medical staff. Methods: A total of 170 dental patients were consecutively included at their regular yearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, the results are consistent with previous research that found that measurement of blood pressure in a dental setting could identify HTN. For example, Friman and colleagues 41 found that about 14% of patients receiving care in a dental setting had diastolic blood pressure values high enough to warrant further follow-up in a medical setting. Furthermore, Greenberg and colleagues 22 found that nearly 20% of patients receiving care in the University of Medicine and Dentistry of New Jersey Dental School were identified as having previously unidentified cardiovascular disease risk factors when their blood pressure and cholesterol were tested and a screening questionnaire was administered in the dental setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are consistent with previous research that found that measurement of blood pressure in a dental setting could identify HTN. For example, Friman and colleagues 41 found that about 14% of patients receiving care in a dental setting had diastolic blood pressure values high enough to warrant further follow-up in a medical setting. Furthermore, Greenberg and colleagues 22 found that nearly 20% of patients receiving care in the University of Medicine and Dentistry of New Jersey Dental School were identified as having previously unidentified cardiovascular disease risk factors when their blood pressure and cholesterol were tested and a screening questionnaire was administered in the dental setting.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also presented that dental settings could be a health promotion entry point into medical care for individuals not previously engaged with a primary care provider [ 30 ]. The cooperation between dental and medical care has proven to be an effective way to discover unknown hypertension [ 11 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in medical screening in dental settings during the early 2000s has been extensive [ 8 11 ], and the activities to identify individuals with undiagnosed diabetes mellitus type II or undiagnosed hypertension have been positively received by patients and dentistry, and have shown to be cost-effective by achieving savings and health benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small town in central Sweden, medical screening for blood pressure and plasma glucose was offered consecutively to 207 regular adult dental patients at their annual check-up, of whom 170 agreed to participate. Thirty-nine patients were referred to health care as possibly at risk of hypertension or diabetes, and 24 of these received further medical treatment or lifestyle recommendations [17].…”
Section: Introductionmentioning
confidence: 99%